1960: Nova Iorque, Londres, Paris e São Paulo - Shitara, Mitsuko (2010)
This thesis analyzes the evolution of fashion and the influences that have suffered and induced on the society of consumption in the 1960s. After surveying of the conditions that led to the development of fashion until the 1960s, illustrated by the evolution of design and ways of production and the raise of an important new category of consumer the youth -, it is recorded the way clothing is consumed, replacing the elitism of Haute Couture for the democracy of Prêt-à-Porter. It also analyzes the major cities in terms of scale of production and consumption of clothing, namely New York and its ready-to-wear, the youth boom in London and the prêt-à-porter that carried the signature of great designers of Haute Couture in Paris. From these cities, it is presented the reality of Sao Paulo, the emergence of a fashion with its own personality, although still strongly influenced by design and production practiced abroad, and how Rua Augusta in the 1960s has became the right site to know the big news at first hand